Assessment of traditional and non-traditional risk factors for premature atherosclerosis in children with juvenile dermatomyositis and pediatric controls - Dawn M. Wahezi; Emily J. Liebling; Jaeun Choi; Marija Dionizovik-Dimanovski; Qi Gao; Jillian Parekh (BMC, 2020)
Abstract Background Children with juvenile dermatomyositis (JDM), the most common inflammatory myopathy of childhood, may be at increased risk of premature atherosclerosis given a host of traditional and non-traditional risk factors. The primary aim of this study was to determine the underlying frequency of premature atherosclerosis in children with JDM compared to pediatric controls using flow-mediated dilation as a measure of endothelial function. Methods Children and adolescents with and without JDM were evaluated for traditional atherosclerotic risk factors and assessment of endothelial function, using Endothelial Pulse Amplitude Testing (Endo-PAT). Results In this study, 75% of pediatric controls were of Black or Hispanic descent (compared to 55% in the JDM group) and 70% were found to live in a household with a medium income less than $50,000/year (compared to 45% in the JDM group). Among traditional atherogenic risk factors, lipoprotein A appeared to be different between controls and JDM patients (66 nmol/L and 16.5 nmol/L, respectively). Using a reactive hyperemia index (RHI) < 1.67 as evidence of endothelial dysfunction, 75% of controls were defined as having endothelial dysfunction compared to 50% in JDM group. When controlled for lipoprotein A as an atherogenic confounder, JDM patients were found to have a 41% increase in RHI, thus indicating less endothelial dysfunction compared to controls. Conclusions In this study, we have shown that atherogenic risk factors are present in the pediatric population and may be associated with endothelial dysfunction, even at very young ages. Despite increasing concerns that children with rheumatologic disorders may be at increased risk of developing premature atherosclerosis, traditional and sociodemographic features may play a greater role in the ultimate development of cardiovascular disease.